Dynamics of heart rate variability in patients with type 2 diabetes mellitus during spinal anaesthesia: prospective observational study - Lee, Su Hyun (BMC Anesthesiol, 2015)
BACKGROUND: Little is known about the changes in autonomic function during spinal anaesthesia in type 2 diabetic patients. The purpose of the study was to assess the influence of spinal anaesthesia on the heart rate variability in type 2 diabetic patients according to the glycated hemoglobin (HbA(1c)) level. METHODS: Sixty-six patients who were scheduled for elective orthostatic lower limb surgery were assigned to three groups (n = 22, each) according to HbA(1c); controlled diabetes mellitus (HbA(1c) < 7 %), uncontrolled diabetes mellitus (HbA(1c) > 7 %) and the control group. The heart rate variability was measured 10 min before (T0), and at10 min (T1), 20 min (T2) and 30 min (T3) after spinal anaesthesia. RESULTS: Before spinal anaesthesia, total, low-and high-frequency power were significantly lower in the uncontrolled diabetec group than in other group (p < 0.05). During spinal anaesthesia, total, low- and high-frequency powers were did not change in the uncontrolled diabetec group while the low-frequency power in the controlled diabetec group was significantly depressed (p < 0.05). The ratio of low-to high-frequency was comparable among the groups, while it was reduced at T1-2 than at T0 in all the groups. The blood pressures were higher in the uncontrolled diabetec group than in the other groups. CONCLUSIONS: Spinal anaesthesia had an influence on the cardiac autonomic modulation in controlled diabetec patients, but not in uncontrolled diabetec patients. There were no differences in all haemodynamic variables during an adequate level of spinal anaesthesia in controlled and uncontrolled type 2 DM. TRIAL REGISTRATION: ClinicalTrials.gov NCT02137057 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12871-015-0125-6) contains supplementary material, which is available to authorized users.